Let the punishment fit the criminal: An experimental study - Montag, Josef; Tremewan, James (Journal of economic behavior & organization, 2020)
•We find people condition punishment on the subjective experience of punishees.•This holds for monetary and non-monetary punishment.•Fines and non-monetary punishments differ in terms of punishee subjective experience.•Fines and non-monetary punishments do not differ as proportion of maximum punishment. We use a laboratory experiment to study the extent to which people tailor levels of punishment to the subjective experience of the person to receive that punishment, for both monetary and non-monetary sanctions. We find that subjects tend to apply higher fines to wealthier individuals. Additionally, subjects assign more repetitions of a tedious task to those with a lower willingness to pay to avoid it. We find no evidence that the distributions of monetary and non-monetary punishments are different when considered as proportions of the maximum possible punishment, but that this does not hold when non-monetary punishments are converted into monetary equivalents. This suggests that subjects do not have in mind a particular level of disutility from the punishment, but rather are guided by the sentencing possibilities.